Development of the OPAL prediction model for prediction of live birth in couples with recurrent pregnancy loss: protocol for a prospective and retrospective cohort study in the Netherlands - Nan van Geloven; Madelon van Wely; Marie-Louise van der Hoorn; Annemarie Mulders; Eileen Lashley; Mariette Goddijn; Angelos Youssef; Rik van Eekelen; Myrthe A J Smits; Jan MM van Lith (BMJ Open, 2022)
Introduction Recurrent pregnancy loss (RPL) is defined as the loss of two or more conceptions before 24 weeks gestation. Despite extensive diagnostic workup, in only 25%–40% an underlying cause is identified. Several factors may increase the risk for miscarriage, but the chance of a successful pregnancy is still high. Prognostic counselling plays a significant role in supportive care. The main limitation in current prediction models is the lack of a sufficiently large cohort, adjustment for relevant risk factors, and separation between cumulative live birth rate and the success chance in the next conception. In this project, we aim to make an individualised prognosis for the future chance of pregnancy success, which could lead to improved well-being and the ability managing reproductive choices.Methods and analysis In this multicentre study, we will include both a prospective and a retrospective cohort of at least 931 and 1000 couples with RPL, respectively. Couples who have visited one of the three participating university hospitals in the Netherlands for intake are eligible for the study participation, with a follow-up duration of 5 years. General medical and obstetric history and reports of pregnancies after the initial consultation will be collected. Multiple imputation will be performed to cope for missing data. A Cox proportional hazards model for time to pregnancy will be developed to estimate the cumulative chance of a live birth within 3 years after intake. To dynamically estimate the chance of an ongoing pregnancy, given the outcome of earlier pregnancies after intake, a logistic regression model will be developed.Ethics and dissemination The Medical Ethical Research Committee of the Leiden University Medical Center approved this study protocol (N22.025). There are no risks or burden associated with this study. Participant written informed consent is required for both cohorts. Findings will be published in peer-reviewed journals and presentations at international conferences.Trial registration number NCT05167812.